SIFAT TRANSPARANSI DAN PERMEABILITAS FILM BIONANOKOMPOSIT POLYLACTIC ACID DAN POLYCAPROLACTONE DENGAN PENAMBAHAN NANOCRYSTALLINE CELLULOSE SEBAGAI PENGISI [Transparency and permeability properties of Bionanocomposite Film of Polylactic Acid and Polycaprolactone, and Nanocrystalline Cellulose as a Filler] - Eti Indarti; Arisa Sri Marlita; Zaidiyah Zaidiyah (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2020)
Production of Polylactic acid (PLA)/Polycaprolactone (PCL) bionanocomposite films with various ratios was done by adding nanocrystalline celullose (NCC) from oil palm empty fruit bunches (OPEFB) as a filler. The aim of the research was to find out the effect of PLA/PCL ratio on film thickness, transparency of bionanocomposite films and water vapor permeability or WVP of the film bionanocomposite with addition of the 3% NCC. The PLA/PCL ratio are 1.0/0.0; 0.8/0.2; 0.6/0.4; 0.5/0.5; 0.4/0.6; 0.2/0.8; and 0.0/1.0, prepared with solvent casting method. Characterization of PLA/PCL bionanocomposites film performed was thickness, transparency test and water vapor permeability (WVP) test. The thickness of bionanocomposites film produced were around are about 0.036-0.053 mm, results show that the lower PLA/PCL ratio the thicker film obtained. The highest value of film transparency was obtained at a ratio of 1.0 / 0.0 (81.4% at a wavelength of 550 nm), the smaller the PLA / PCL ratio, the lower the value of transparency. The WVP value of PLA/PCL bionanocomposite films gives a lower value than the WVP value of pure PLA film and pure PCL film. The best WVP was obtained at a PLA/PCL ratio of 0.8/0.2 which was 1.49x10-16kg.m/(m2.s.Pa).